2019
DOI: 10.1177/1521025119833000
|View full text |Cite
|
Sign up to set email alerts
|

Academic Success and 1 Year of Intramural Sports Participation by Freshmen Students

Abstract: The purpose of this study was to investigate differences in academic indicators among intramural sports participants and nonparticipants following their first year of college. Matched samples (N = 1,796; 898 pairs) were generated based on demographic variables. Data were obtained from university databases. Paired sample t tests and logistic regression were used to assess differences between participants and nonparticipants. First-semester and first-year grade point average were significantly higher (p < .001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…For example, Kulp et al (2019) found that first year students who participate in extracurricular activities (e.g., intramural sport) experience greater academic success and higher retention rates. Further, Forrester et al (2018) found that participation in intramural sport resulted in greater student retention when compared to the broader undergraduate student population (see also Vasold et al, 2021). Many scholars attribute this to Astin's (1984) theory of student involvement suggesting involvement in extracurricular activities (such as campus recreation) contributes to continued persistence in postsecondary education (Elkins et al, 2011;Forrester, 2015;Henchy, 2013).…”
Section: Campus Recreation Program Satisfaction and Student Retentionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, Kulp et al (2019) found that first year students who participate in extracurricular activities (e.g., intramural sport) experience greater academic success and higher retention rates. Further, Forrester et al (2018) found that participation in intramural sport resulted in greater student retention when compared to the broader undergraduate student population (see also Vasold et al, 2021). Many scholars attribute this to Astin's (1984) theory of student involvement suggesting involvement in extracurricular activities (such as campus recreation) contributes to continued persistence in postsecondary education (Elkins et al, 2011;Forrester, 2015;Henchy, 2013).…”
Section: Campus Recreation Program Satisfaction and Student Retentionmentioning
confidence: 96%
“…Scholars suggest that participants are likely to experience social outcomes as evidenced by improved communication skills, respectful behavior, and expanding social networks (Cooper et al, 2012;Phipps et al, 2015;Sturts & Ross, 2013). Participation in intramural sport has also been associated with intellectual benefits (Lower et al, 2013), increased grade point averages (Vasold et al, 2021), and improved soft skills (e.g., critical thinking, cooperation) (Sturts & Ross, 2013;Williams et al, 2018). Together, existing research points to the various health and wellness, and learning outcomes that have been attributed to participation in intramural sport, while highlighting the importance of intramural programming across postsecondary contexts.…”
Section: Benefits Of Intramural Sport Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other single intuitional studies controlled for student characteristics while examining the relationships among academic outcomes and intramural sports (Vasold et al, 2019a) and club (Kampf & Teske, 2013) participation. Some multivariate analytic studies have relied on self-reported measures (i.e., using a survey) of student participation across multiple institutions (Vasold et al, 2019b). All studies examining club and intramural sports defined participation as binary; if the student participated in a game or reported participation, they were counted as a participant.…”
Section: Campus Recreation and Academic Outcomesmentioning
confidence: 99%
“…Research has examined use of recreation facilities, as well as participation in club and intramural sports. Studies have found campus recreation participants have higher grade point averages (GPAs), retention rates, and graduation rates (Belch et al, 2001; Danbert et al, 2014; Huesman Jr et al, 2007, 2009; Leppel, 2005; Mayers et al, 2017; McElveen & Ibele, 2019; Roddy et al, 2017; Vasold et al, 2019a; Vasold et al, 2019b; Zegre et al, 2020). Beyond institutional outcomes, benefits of campus recreation include physical and mental health outcomes (Brock et al, 2015; Forrester, 2014; Zizzi et al, 2004); Forrester (2014) reported nationwide evidence of positive associations between campus recreation and a range of outcomes including student enrollment, retention, academics, employment, health, and wellness.…”
Section: Using a Data-driven Approach To Examine Facility Use Definit...mentioning
confidence: 99%